2019
DOI: 10.1186/s13046-019-1117-z
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-rich intestinal protein 1 suppresses apoptosis and chemosensitivity to 5-fluorouracil in colorectal cancer through ubiquitin-mediated Fas degradation

Abstract: Background Cysteine-rich intestinal protein 1 (CRIP1) is highly expressed in human intestine and aberrantly expressed in several types of tumor. However, studies on CRIP1 are limited and its role on tumor development and progression remains controversial and elusive. Methods Immunohistochemistry was performed to evaluate the expression of CRIP1 in paired normal and colorectal tumor specimens, as well as colorectal cell lines. Functional assays, such as CCK8, TUNEL assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 40 publications
0
38
1
Order By: Relevance
“…Here we identified CRIP1 as a new posttranscriptional modifier of RAD51. However, in contrast to the findings of Zhang et al [ 11 ] that CRIP1 promotes ubiquitination and degradation of Fas, exogenous overexpression of CRIP1 dramatically inhibited RAD51 ubiquitination levels, suggesting that CRIP1 itself does not possess ubiquitin ligase activity. The regulatory effect of CRIP1 on protein ubiquitination levels is indirect and mainly depends on the protease activity of ubiquitinases or deubiquitinases regulated by CRIP1.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Here we identified CRIP1 as a new posttranscriptional modifier of RAD51. However, in contrast to the findings of Zhang et al [ 11 ] that CRIP1 promotes ubiquitination and degradation of Fas, exogenous overexpression of CRIP1 dramatically inhibited RAD51 ubiquitination levels, suggesting that CRIP1 itself does not possess ubiquitin ligase activity. The regulatory effect of CRIP1 on protein ubiquitination levels is indirect and mainly depends on the protease activity of ubiquitinases or deubiquitinases regulated by CRIP1.…”
Section: Discussioncontrasting
confidence: 98%
“…Cysteine-rich intestinal protein 1 (CRIP1), a member of the LIM/double-zinc finger protein family, is overexpressed and associated with prognosis in several tumor types [ 7 11 ]. However, its functional role functional role of CRIP1 in cancer biology is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is a tightly controlled process, characterized by three pathways, namely, the mitochondrial [ 28 ], endoplasmic reticulum [ 51 ] and death receptor signaling pathways [ 28 ]. Interestingly, Zhang et al have demonstrated, in several cancer cell lines, that the oncoprotein Cysteine-rich intestinal protein 1 (CRIP1) can interact with Fas, enhancing its ubiquitination and degradation and leading to inhibition of caspases 8 and 3, thus underlining the tumor suppressor role of this transmembrane protein [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of CRIP1 expression after successful treatment is similarly unknown. CRIP1 is a zinc-binding protein with high expression in immune cells and epithelium that may play a role in DNA damage repair 18,37,38 . Its role in allograft recovery after ACR requires further study.…”
Section: Discussionmentioning
confidence: 99%